CRP 2020 Reviews: Rice Agri-Food Systems (RICE) - Kumar, Ravinder; Yadav, Rattan (CGIAR Advisory Services, 2020)
In 2020 the CGIAR CAS Secretariat is conducting independent reviews of the 12 CGIAR Research Programs (CRPs), including this one of RICE. The reviews will provide information on quality of science and effectiveness in each CRP. This review covers the Phase II years of 2017 through 2019, with a view to identifying lessons for future research modalities.